Pengaruh Permainan Tradisional Terhadap Keterampilan Motorik Halus Anak Usia 4-5 Tahun (Penelitian Quasi Eksperimen di TK Plus Manar Al–Ummat) - Ilfiani Alfanisa; Lutfi Nur; Gilar Gandana (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2026)
This study aims to determine the effect of traditional games on the fine motor skills of children aged 4–5 years at Manar Al-Ummat Plus Kindergarten. Traditional games such as congklak and marbles are believed to be effective and fun media to stimulate children's fine motor skills, especially in eye-hand coordination, as well as manipulative skills. This study used a quantitative approach with a quasi-experimental design involving two groups, namely the experimental class that received treatment in the form of traditional games and the control class without such treatment. The sample consisted of 20 children divided equally into two groups. Data collection was carried out through pretests and posttests using fine motor skills observation sheets based on STPPA indicators (Permendikbud No. 137 of 2014). The results of the analysis showed a significant increase in children's fine motor skills in the experimental class compared to the control class. Thus, traditional games are proven to have a positive influence in developing fine motor skills in early childhood and can be used as an alternative learning method based on local culture that is contextual and educational